Pelatihan Pengelolaan Sampah Rumah Tangga dengan Cara Pilah Sampah di Desa Pidodowetan Kabupaten Kendal - M Ghufron Abusamah; Wahjoerini Wahjoerini (Jurnal Pengabdian KOLABORATIF, 2023)
The increasing consumption value of urban communities in meeting their daily needs is a contributor to the increasing amount of waste that must be disposed of. Household waste cannot be considered small in terms of the capacity of waste contributors to the environment. The problems faced by partners, namely residents of RT 01 RW 03 of Pidodowetan Village, Patebon District, Kendal Regency, are mainly related to sorting, separating, handling, and managing household waste. A strategic handling of waste management is needed. The government has taken various actions toward handling and managing waste, it's just that it hasn't touched the lowest level of handling, namely household waste. The purpose of community service activity is to provide training and outreach to the community to be able to sort waste and recognize types of waste that have economic value so that they can be saved in a waste bank, and only types of residue may enter the Final Processing Site (TPA). The implementation method used is in the form of lectures as well as discussions and direct practice with partners. In this activity, the results showed that there was a change, some members of the community were able to sort household waste. Partners do not experience significant obstacles because they have received provisions in counseling related to the sorting and economic use of waste, both organic and inorganic waste. In the future, it is expected to make the cleanliness of the surrounding residential environment better.